Violence against Women: Comparing Female Genital Mutilation and Female Circumcision in Malaysia - Norazam Khair Mohd Ithnin; Ishak Suliaman; Abdul Halim Ibrahim (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The United Nations (UN) General Assembly resolution on 20 December 2012 declared female genital mutilation (FGM) illegal and a violation of women's rights. This declaration was made following the World Health Organization's (WHO) call to eradicate FGM in 1997. The prohibition includes all forms of mutilating, harming, or causing pain to the female genitalia. The female circumcision practice in Malaysia is also categorized as FGM by the United Nations Human Rights (UNHR) at the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) in 2018. In light of these developments, this qualitative study examines and compares the true nature and concepts of FGM and the female circumcision practice from the perspective of Al-Sunnah Al-Nabawiyyah. Documentation was employed for data collection, analysis, and interpretation. The findings reveal a significant divergence between FGM and female circumcision. Female circumcision is more similar to the aesthetic surgery of the female genitalia, known as clitoral hood reduction, which can enhance women's sexuality. In conclusion, female circumcision in Malaysia is not a torturous act that violates women's rights, but rather a safe practice following Islamic law. This study also proposes a comprehensive research initiative aimed at formulating secure and Sharia-compliant protocols for female circumcision.